Conjugation of chlorins with spermine enhances phototoxicity to cancer cells in vitro - Darmostuk, Mariia; Jurášek, Michal; Lengyel, Kamila; Zelenka, Jaroslav; Rumlová, Michaela; Drašar, Pavel; Ruml, Tomáš (Journal of photochemistry and photobiology. B, Biology, 2017)
Photodynamic therapy (PDT) is one of the most promising methods of specific cancer treatment. However, commercially available photosensitizers (PSs) show significant drawbacks, such as side toxicity, low penetration ability, low blood solubility, low tumor selectivity etc. In addition, as was shown previously, a conjugation of polyamines with several toxic agents led to an increased toxicity to cancer cells. Here, we synthesized conjugates of two chlorine photosensitizers, purpurin 18 and pheophorbide a, with spermine in natural and Boc-protected form. Using specialized software, we calculated octanol-water partition coefficients for single protonation state (logP) of single PSs and PS/spermine conjugates. We found that the addition of spermine to chlorine PSs shifted the logP towards higher hydrophilicity in comparison to logP of single chlorines. In vitro studies on several cancer cells indicated that conjugation of purpurin 18 with spermine increased its retention in cancer cells. Using various concentrations of this conjugate, we found that lower concentrations (under 0.2μM) of purpurin 18/spermine conjugate launched apoptosis in HeLa cells. This combined with its high phototoxicity makes the purpurin 18/spermine conjugate a promising photosensitizer for PDT. Obtained results might serve as a basis for further studies of this potential third-generation PS on mammalian models in vivo.
Keywords: Animals; HeLa Cells; apoptóza; Porphyrins; Cell Line, Tumor; porfyriny; Apoptosis; Spermine; nádorové buněčné linie; lidé; HeLa buňky; Photochemotherapy; Photosensitizing Agents; chlorofyl; fotosenzibilizující látky; Humans; spermin; zvířata; fotochemoterapie; Chlorophyll; hydrofobní a hydrofilní interakce; Hydrophobic and Hydrophilic Interactions